TREM1/3 Deficiency Impairs Tissue Repair After Acute Kidney Injury and Mitochondrial Metabolic Flexibility in Tubular Epithelial Cells - Tammaro, Alessandra; Scantlebery, Angelique M. L.; Rampanelli, Elena; Borrelli, Cristiana; Claessen, Nike; Butter, Loes M.; Soriani, Alessandra; Colonna, Marco; Leemans, Jaklien C.; Dessing, Mark C.; Florquin, Sandrine (Frontiers in Immunology, 2019)
Long-term sequelae of acute kidney injury (AKI) are associated with incomplete recovery of renal function and the development of chronic kidney disease (CKD), which can be mediated by aberrant innate immune activation, mitochondrial pathology and accumulation of senescent tubular epithelial cells (TECs). Herein, we show that the innate immune receptor Triggering receptor expressed on myeloid cells-1 (TREM-1) links mitochondrial metabolism to tubular epithelial senescence. TREM-1 is expressed by inflammatory and epithelial cells, both players in renal repair after ischemia/reperfusion (IR)-induced AKI. Hence, we subjected WT and TREM1/3 KO mice to different models of renal IR. TREM1/3 KO mice displayed no major differences during the acute phase of injury, but increased mortality was observed in the recovery phase. This detrimental effect was associated with maladaptive repair, characterized by persistent tubular damage, inflammation, fibrosis and TEC senescence. In vitro, we observed an altered mitochondrial homeostasis and cellular metabolism in TREM1/3 KO primary TECs. This was associated with G2/M arrest and increased ROS accumulation. Further exposure of cells to ROS-generating triggers drove the cells into a stress-induced senescent state, resulting in decreased wound healing capacity. Treatment with a mitochondria anti-oxidant partly prevented the senescent phenotype, suggesting a role for mitochondria herein. In summary, we have unraveled a novel (metabolic) mechanism by which TREM1/3 deficiency drives senescence in TECs. This involves redox imbalance, mitochondrial dysfunction and a decline in cellular metabolic activities. These finding suggest a novel role for TREM-1 in maintaining tubular homeostasis through regulation of mitochondrial metabolic flexibility.